Application of the model of management of knowledge intelect to the activities of investigation of the IIGEO-UNMSM - Lovera Dávila, Daniel Florencio (2006)
The present presentation tries to show an application of the model «Intelect» to the measurement of the Intellectual Capital in the context of the activities of investigation of the Institute of Investigation IIGEO of the Universidad Nacional Mayor de San Marcos. The mentioned model makes a balance of the intangible elements that has the organization, presenting a process of identification, selection and measurement of assets of systematic way, based on the three capitals (human, structural and relational), making emphasis in its interactivity and evolutionary capacity. Some significant indicators of each capital involved in the model are quantified, which indicates their evolution to us in the time and an analysis of the results to raise necessary corrective measures for the continuous improvement of the management of the knowledge that is developed in the IIGEO.